KEMAMPUAN MOTORIK ATLET SENAM USIA DINI PERSANI SULAWESI SELATAN - Ferawati, Ferawati (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2018)
Motor skills can be developed through sports and play activities involving muscle work. If children do more movement within motor element that they would more trained. With a lot of motor experience will increase the maturity in doing motor activity. Motor skills in this study were observed through endurance levels, speed, power, agility, coordination and balance. This research is a quantitative descriptive research, held in GOR Gymnastic PPLP Sulsel, focus on motor ability of children aged 6-9 years Persani Sulsel as many as 30 people. The instruments used are: (1) run 40 meters, (2) run dodging run, (3) run 600 meters, (4) long jump without prefix, (5) climb the beam of the catwalk, (6) throw tennis ball. In the study obtained data about motor skills athletes gymnastics early age persani sulsel is in the category of GOOD. In the men's category 40% GOOD category and daughter is 33.33% GOOD category